Paris in the terror june 1793 - july 1794 - Loomis, Stanley (Lippincott, 1964)
It was an epoch with far-reaching consequences for the fate of Europe and the world, a teeming drama of bizarre and colourful characters, relics of the old regime and frenzied apostles of the new, thronging the stage of Paris.